Valuing an entrepreneurial enterprise - Audretsch, David B.; Link, Albert N. (New York : Oxford University Press, 2012)
In this work, Audretsch and Link present a valuation method uniquely tailored to emerging technology-based ventures that have no revenue history to lean on. Their method draws on economic theory to formulate a solution to the problem.
Includes bibliographical references and index.
Description based on print version record.
Keywords: New business enterprises -- Valuation; Small business -- Valuation; Entrepreneurship